YIELD AND PROFITABILITY OF SOYBEAN CROP - Paula STOICEA; Mirela Elena DUȘA; Adrian-Gheorghe BĂȘA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Soybean is a crop with major benefits for the environment, under the conditions of using good agricultural practices, by fixing atmospheric nitrogen which reduces fertilization with mineral nitrogen and its leaching. The integration of soybean in the crop rotation is beneficial and can create conditions for its relaunch and long-term viability so that European consumption can be covered and the dependence on imports can be reduced. The case study carried out on two farms in Romania, South - Muntenia Region, highlighted that, under irrigation conditions, this crop had productions of over 4,000 kg/ha. The capitalization price increased during the analysis period, so the farms recorded a positive and ascending result in the period 2019-2021, except the 600 ha farm, which in 2019, recorded a loss because the crop was not irrigated and the production average (1,712 kg/ha) was insufficient for profit obtaining.